Implementing the OpenEHR electronic medical record in content management systems: Similarity between archetypes and content - Pessanha, Christiano Pereira (Seven Editora, 2024)
This article describes doctoral research motivated by the challenges arising from efforts to achieve semantic interoperability in Electronic Health Records (EHRs) via the OpenEHR standard. The research carried out the implementation of OpenEHR information models that provide semantics to archetypes. By evaluating the implementation of EHRs in CMSs compared to implementations made from scratch, the research analyzes the necessary requirements for the implementation of EHRs in CMSs. This theoretical effort allowed to establish a theoretical argumentation, of general scope, regarding the concepts of archetype and types of CMS, which shows the similarity between the concepts of archetype and content. This result establishes a close relationship between these two concepts from different domains, expanding the understanding and possibilities of building this type of software in content management systems, in general. DOI:https://doi.org/10.56238/sevened2024.003-063